2015
DOI: 10.1002/adma.201502866
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Versatile Photonic Annealing of Graphene Inks for Flexible Printed Electronics

Abstract: Intense pulsed light (IPL) annealing of graphene inks is demonstrated for rapid post-processing of inkjet-printed patterns on various substrates. A conductivity of ≈25,000 S m(-1) is achieved following a single printing pass using a concentrated ink containing 20 mg mL(-1) graphene, establishing this strategy as a practical and effective approach for the versatile and high-performance integration of graphene in printed and flexible electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
308
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(316 citation statements)
references
References 42 publications
8
308
0
Order By: Relevance
“…Secor and co-workers proposed a graphene ink-nitrocellulose electrochemical sensor for H 2 O 2 determination [33]. Several works have demonstrated that a post treatment of the graphene ink could improve its conductivity through thermal reduction process [12,34,35]. More specifically, Arapov et al [12], Secor et al [34], and Del et al [35] enhanced graphene ink films to sheet resistances of 1.4 Ω/cm, 21.4 Ω/cm, and 30 kΩ/cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Secor and co-workers proposed a graphene ink-nitrocellulose electrochemical sensor for H 2 O 2 determination [33]. Several works have demonstrated that a post treatment of the graphene ink could improve its conductivity through thermal reduction process [12,34,35]. More specifically, Arapov et al [12], Secor et al [34], and Del et al [35] enhanced graphene ink films to sheet resistances of 1.4 Ω/cm, 21.4 Ω/cm, and 30 kΩ/cm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve high σ, a sintering step is necessary, which typically requires temperatures above that of the dielectric glass transition temperature (T g ) of the dielectric substrate. Surface-sensitive sintering techniques based on photonics have recently become popular in order to circumvent this challenge [23]. Since this type of sintering evolves under nonequilibrium conditions across multiple scales there are not well known, processstructure-property relationships must be developed.…”
Section: Challenges Aheadmentioning
confidence: 99%
“…These methods include Joule heating, [31] microwave irradiation, [12] infra-red heating, [32] and photonic flash annealing. [6,[33][34][35] The latter is a contactless, highly controllable method compatible with highspeed R2R processing and, since it is based on the light absorption, holds great promise for graphene applications.…”
Section: Introductionmentioning
confidence: 99%